Analysis of Maximizing the Power Output of Switched Reluctance Generator Using Different Core Materials - M. Ramkumar; K. Latha (Advances in Materials Science and Engineering)
Switched reluctance generator (SRG) has become the key focus of research for its usage in wind power generation. The sizing and performance of SRG depend on the core material used for the stator and rotor. This paper analyses the impact of the magnetic loading of different core materials on the performance of SRG in terms of self-inductance, torque, iron losses, ohmic losses, and generated voltage. 1 kW SRG with different pole configuration 8/6 SRG and 12/8 SRG for the wind speed of 3 m/s to 6 m/s has been designed. Static and dynamic analyses using the finite element analysis (FEA) were carried out for analytically designed 1 kW SRG with different core materials with the same lamination thickness. Prototypes of 8/6 SRG and 12/8 SRG are fabricated. The output of simulation results has been validated by experimental measurements.